Practical Utility of Serum Ammonia in Children With Acute Liver Failure: A Biomarker of Outcome - Hala Mohsen Abdullatif, MD; Katharina Weigel; Anita Verma, MD; Akash Deep, MD; Anil Dhawan, MD, FRCPCH (Transplantation Direct)
Background. Hyperammonemia is a recognized biochemical abnormality in acute liver failure (ALF). Our aim was to determine a cutoff value for serum ammonia in children with ALF to predict their outcomes while conventional UK liver transplant (LT) listing criteria were applied. Methods. We reviewed and analyzed the data of 68 patients with ALF who presented to our center from January 2014 to December 2018; inherited defects of ammonia metabolism were excluded. Patients were divided into 3 groups: Gr 1, LT (30 patients); Gr2, native liver survival (27 patients); and Gr 3, mortality (11 patients). Results. Highest ammonia levels during admission before intervention were higher in the LT and mortality group than in the native liver survival group (P = 0.011) with levels of 140 µmol/L showing a specificity of 100% as a predictor for LT/mortality. Sixty-two percent of patients with ALF developed encephalopathy; grades 3 and 4 in almost one-third. Encephalopathy was more common in Gr1 patients, followed by Gr3, whereas Gr2 were the least likely to develop encephalopathy. Ammonia levels were significantly higher in encephalopathic patients than in nonencephalopathic (P = 0.001). Serum ammonia of 80.5 µmol/L predicted encephalopathy with 80% sensitivity and 75% specificity. Conclusions. Serum ammonia level of >80 µmol/L can be used as an alert to ongoing encephalopathy although encephalopathy signs may be missing or subtle and a surrogate marker for earlier interventions for extracorporeal therapies. Moreover, levels >140 µmol/L predict the need for LT or death.